Does the effectiveness of money supply and foreign direct investment determine the industrial growth performance in India? - Mrutyunjaya SAHOO; Praveen SAHU (Theoretical and Applied Economics, 2023)

(untitled)
Industry is a primary engine in determining India’s overall economic growth. This study empirically investigated the effects of money supply and foreign direct investment on the industrial growth performance in India by using the method of a multivariate VAR model. The results of the multivariate VAR model indicate a positive effect of foreign direct investment inflows and a negative effect of money supply on industrial growth performance in the long run. Moreover, it is proven that there is a bidirectional causal relation between industrial growth and foreign direct investment inflows and a unidirectional causal relation from money supply to industrial growth in India. Accordingly, the study recommends that an expansionary money supply will improve industrial growth performance over the short run but not in the long run. In contrast, the amount of foreign direct investment will improve the industrial growth performance over the short-run as well as the long-run.